(untitled) (Journal of Naval Architecture and Marine Engineering, 2022)
Inventory models for deteriorating items of a supply chain is of critical essence to the maritime industry. This study proposes a real and economically efficient multicriteria inventory policy of inventory models for deteriorating items of a supply chain with nonlinear ramp functions and permissible delay in payment under inflation, two conditions Shortages Followed by Inventory (SFI) and Inventory Followed by Shortages (IFS) have been considered for the formulation of models. Both the models consist of ordering cost, unit cost, deterioration cost, shortage cost and holding cost with replenishment where delay in payments is allowed. The development of these models is to minimize the total average cost per unit time. In order to validate the models, numerical examples have been considered and the sensitivity of several major parameters of exponential and quadratic functions is analyzed. From the numerical result, it is clear that the cost per unit time of IFS model decreases with the increment of the values of parameters of the quadratic function and holding cost whereas, with the increment of the values of parameters of the exponential function as well as holding cost per unite time, the cost per unit time of SFI model decreases. However, if the values of the parameters of the exponential functions as well as ordering cost and shortage cost increase, the cost per unit time of IFS model increases. On the other hand, it will also increase considering SFI condition, if the values of parameters of the quadratic function as well as ordering cost and shortage cost increase. Finally, it is observed that the model considering IFS case works better than SFI model up to a certain level.